Choledochal Cyst: Their clinical presentation, diagnosis and treatment in central Nepal: a retrospective study - Kumar, Sujit; Jalan, Aditya; Patowary, Bhupendra Nath (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Choledochal cyst is a rare congenital malformation involving the cystic dilatation of intrahepatic and/ or extra-hepatic bile duct. The estimated incidence is one in 1000 live birth in Asian population with female to male ratio 3:1. The objective of the study was to study the presentation, diagnosis, treatment and outcome of choledochal cyst in College of Medical Sciences, Bharatpur, Nepal Materials & Methods: A retrospective review of the records of all the patients who were diagnosed as choledochal cyst and underwent medical or operative intervention in our hospital from January 2013- January 2015. Results: We analyzed ten cases of choledochal cyst. The condition commonly affected the age group was six to 10 years with and female preponderance (70%). Most common presenting symptom was pain abdomen (100%) and jaundice (50%). However classical triad of abdominal pain, jaundice, and an abdominal mass was not seen in any of the cases. Ultrasonography was diagnostic in all cases. Todani type I cyst was the most common type. Nine out of ten cases underwent complete cyst excision with cholecystectomy and Roux-en-Y hepaticojejunostomy without any major complication. Conclusion: Choledochal cyst is a clinical condition that is conveniently diagnosed on ultrasound and has a rewarding outcome if operated